Perceived Challenges of Artificial Intelligence in Healthcare among Undergraduate Medical Students at a Public Medical School in Sarawak, Malaysia - Chau Chung, Chai; Md Mizanur, Rahman; Karen Shendy, Sampson Sambong; Siti Nursyazwani, Azmi Murad; Hariz Hizami, Hatta; Chai Zi, Penny Chen (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2024)
Introduction: As artificial intelligence (AI) becomes more integrated into healthcare, it also brings challenges. Understanding these perceived challenges among medical students is crucial for developing educational frameworks that prepare them to navigate these challenges in clinical practice. However, the perceived challenges of AI in healthcare among medical students in Sarawak, Malaysia, remain underexplored. Aim/Purpose/Objective: This study aimed to assess the perceived challenges of AI in healthcare among undergraduate medical students at a public medical school in Sarawak, Malaysia.